Splenogonadal fusion: A rare paratesticular lesion and how to recognise it on ultrasound. (February 2020) - Seager, Matthew John; Alexander, Sarah; Muneer, Asif; Walkden, Miles
Introduction: Splenogonadal fusion is a rare developmental disorder that results in a gonadal or paragonadal mass due to the close proximity of the developing spleen and gonad. Case report: We describe a case of splenogonadal fusion presenting as a paratesticular mass in a 25-year-old male. This was ultimately diagnosed on surgical biopsy. Discussion: Splenogonadal fusion is a rare abnormality but can be managed conservatively. The sonographic features and the differential diagnosis are highlighted. Conclusion: Through this case, we highlight the clinical and sonographic features of splenogonadal fusion. Awareness amongst ultrasound practitioners is important, given that it can be managed conservatively, and means of a non-invasive diagnosis are highlighted.